Comparative Analysis of Pricing and Features of Cloud-Based Accounting Software in Indonesia: A Study of Secondary Data from E-Marketplace - Surateman Surateman; Wahyo Wahyo; Jooner Rambe (Pusat Riset dan Inovasi Nasional, 2025)
The development of cloud technology itself has encouraged digitalization in various sectors, including accounting. In Indonesia, for example, more and more businesses—especially micro, small, and medium enterprises (MSMEs)—have begun to switch to using cloud-based accounting software to improve the efficiency, accuracy, and accessibility of financial management. This transition is not only driven by the need for real-time data and automation but also by the increasing availability of affordable internet infrastructure and government support for MSME digital transformation. This study aims to conduct a comparative analysis of the price and main features of four popular cloud accounting software in Indonesia, namely Beecloud, Jurnal by Mekari, Accurate Online, and Kledo. These four platforms have been selected based on their popularity, user base, and relevance for MSMEs in Indonesia. The data for this study was collected secondarily through each provider’s official website and publicly available documentation during the period of May 1–5, 2025. The method used is a descriptive-comparative quantitative approach, which involves analysis techniques such as descriptive statistics, price-per-feature ratio calculations, and data visualization tools including tables, bar charts, heatmaps, and scatter plots. This approach allows for a comprehensive understanding of both the cost structure and functional range of each product. The results show that there are significant differences in pricing models and the number of features offered. Beecloud SME offers the lowest price-per-feature ratio, suggesting high value for cost-conscious users. On the other hand, Jurnal Enterprise has the highest ratio, indicating a more premium pricing strategy that may be more suitable for medium to large enterprises with more complex needs.